E-Learning and sustainability in higher education: An international case study - Isaias, P.; Issa, Tomayess (Common Ground, 2013)
The learning management systems (LMS) facility has become an essential tool in teaching and learning processes for higher education, since this tool assists students and lecturers to interact, communicate, collaborate, and corporate, and this can lead to cultivating and improving students’ communication skills. Currently, the majority of universities nationally and internationally are using LMS (Blackboard and Moodle) for uploading unit materials, including assessment tasks. This study will assess LMS from a different angle by examining lecturers’ and students’ attitudes to it as a means of submitting assessment tasks with the traditional method. Using the LMS facility for the submission of assessment tasks can assist students as well lecturers to reduce the amount of materials being used (such as paper) and preserve resources; moreover, the cost of binding and delivery will be reduced or eliminated since all submissions are made automatically. This study provides an answer to the question “Do assessment tasks submissions made via learning management systems (LMS) and email increase sustainability awareness among Information Systems students in Portugal and Australia?"The answer was obtained through informal student feedback (N=63) containing quantitative and qualitative data. The findings indicated that a win-win situation is created since lecturers are delighted that e-learning sustainability principles are being successfully promoted in their teaching and learning approaches, since all communications between students are established via email, blackboard and Moodle forums. Furthermore, the research study confirmed that the uploading of assessment tasks via LMS and email facilities is easier, inexpensive, convenient and less time-consuming compared with the traditional methods of submission and feedback. In addition, this method is more sustainable (as fewer materials are used), practical and cheaper, as these principles are aligned with those of the Sustainability and E-learning (SeL) Model.